Knowledge based urban development: An approach to innovation districts based on education - Ponce-Lopez, Roberto; Peraza-Mues, Gonzalo; Gómez-Zaldívar, Fernando; Membrillo-Hernández, Jorge; Acuña-López, Alejandro; Caratozzolo, Patricia (Frontiers in Education, 2023)
Education is a concept that encompasses not only the teaching-learning process but also the conditions, environment, and facilities in which it takes place. Education is a precondition to development because it serves as a society’s primary engine of innovation. Therefore, the concept of a space designated as an Innovation District is essential for the creation of Sustainable Cities since it is in such spaces that jobs are created and new markets specializing in products and high-added value services emerge. However, in the past, successful innovation districts have generally been found in developed countries, which have sufficient resources to invest in projects of this magnitude. Our methodology consists of a case study, the city of Querétaro, in central Mexico, to analyze the role of higher education within developing countries that seek to create innovation districts. We employ quantitative methods such as Geographic Information Systems (GIS) and locations quotients, along with qualitative documentary analysis, to conduct a spatial-urban analysis, characterize the industrial configuration, and to analyze the design of educational models adapted to the needs of specific industries. The results of our case study suggest that cities from developing countries that are fast industrializing can best maximize their chances of success by encouraging an explicit collaboration between industry and education through a Triple Helix Model. Such a collaboration would be based on matching educational competencies with opportunities for industrial reconfiguration to carefully select the location for the new district and decide over its area of specialization.